(untitled) (Medico Legal Update, 2020)
Cross sectional research design study was conducted to “Assessment of the risk factor and incidence of low back pain among higher secondary students selected school at Kanchipuram District, Tamil Nadu, India”. The objectives of the study were to assess the demographic variables with the risk factors of low back pain. To assess the incidence of low back pain among higher secondary school students. To associate the risk factors and incidence of low back pain among higher secondary school students with elected demographic variables. Convenient sampling technique was followed and 102 higher secondary students selected school who met inclusion criteria were in the higher secondary school students participate from the class 11th to 12th. Students who are available in data collection student who can read and understand Tamil/English. The collected data were formulated and analysed by using cross sectional research design and inferential statistics. Result shows, that Maximum no of low back pain in secondary school students were in the age group of 59(84%), among sex of male participated were 53(52%) are low back pain secondary school student majority of playing participation in the games was “Yes” 96(94%),majority of low back pain for secondary school students hobbies like sports 62(61%), among the this students maximum height are 55(54%) and maximum weight of the students 58(57%), the majority of students BMI 58(57%), are low back pain in secondary school students bag weight of 79(77%). There is significant association of assessment of the risk factor and incidence of low back pain among higher secondary school students with demographic variables like participation in the games, bag weight. But there is no significant of assessment of the risk factor and incidence of low back pain among higher secondary school students.